Physics of Bamboo Rifle: Improving Data Literacy Through a Project-Based Learning Laboratory with an Ethno-STEM Approach - Ubaidillah*, Mujib; Mulyani, Asep; Wibowo, Aldi Alfiansyah; Yosriah, Ely (Jurnal IPA & Pembelajaran IPA, 2025)
Data literacy is an essential part of 21st-century skills learning. The rapidly developing digital era currently presents much data-supporting work. This study aimed to improve data literacy through a project-based learning laboratory (PjBL-Lab) with an ethnoscience-science, technology, engineering, and mathematics (ethno-STEM) approach in bamboo rifle physics learning. The research method used a quasi-experiment with a sample of 62 students from the experimental class and 65 students from the control class. The research population was students in the first semester of biology education at a state Islamic university in West Java and science education students at a state Islamic university in Central Java, totaling six classes with a total of 188 students. The sampling technique used was random sampling. The data literacy test instrument used descriptive questions with a rubric that meets valid and reliable criteria. A questionnaire was used to measure the practicality of the learning model's implementation. Data analysis used N-Gain and the non-parametric Mann-Whitney U statistical test. The results showed that data literacy can be improved by implementing the PjBL-Lab learning model integrated with ethno-STEM. There was a significant difference in data literacy abilities between the two classes. The PjBL-Lab model with an ethno-STEM approach received a positive response from students. Therefore, the PjBL-Lab model integrated with ethno-STEM can improve data literacy and is practical for learning. Future research can explore traditional games that can be integrated into physics learning to enhance various 21st-century skills.